2020
DOI: 10.7150/ijms.47299
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined Epidural-general Anesthesia on Hemodynamic Instability during Pheochromocytoma and Paraganglioma Surgery: A multicenter retrospective cohort study

Abstract: Objectives: The purpose of this study was to compare the effects of combined epidural-general anesthesia with those of general anesthesia alone on hemodynamic instability (intraoperative hypotension and hypertensive crisis) during pheochromocytoma and sympathetic paraganglioma surgery. Methods: A total of 119 patients' medical records were reviewed who were diagnosed as having pheochromocytoma and sympathetic paraganglioma on the basis of histological findings. Intraoperative hypotension was defined as a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The characteristics of included studies were shown in Table 1 . These 3 studies were published from 2018 to 2020, performed in China, [ 18 ] Korea, [ 16 ] and America, [ 17 ] respectively. The surgery types of the included studies were open surgery of pheochromocytoma, [ 18 ] open surgery of pheochromocytoma or paraganglioma, [ 17 ] and laparoscopic or open surgery of pheochromocytoma or paraganglioma, [ 16 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies were shown in Table 1 . These 3 studies were published from 2018 to 2020, performed in China, [ 18 ] Korea, [ 16 ] and America, [ 17 ] respectively. The surgery types of the included studies were open surgery of pheochromocytoma, [ 18 ] open surgery of pheochromocytoma or paraganglioma, [ 17 ] and laparoscopic or open surgery of pheochromocytoma or paraganglioma, [ 16 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, epidural anesthesia in laparoscopy may not be appropriate, as it only provides a segmental block, which would not give an adequate pain relief during gas insufflation to create pneumoperitoneum. Additionally, it was reported that the combined epidural-general anesthesia during laparoscopy was not effective in attenuating hypertensive responses, and could have exacerbated intraoperative hypotension [12].…”
Section: Discussionmentioning
confidence: 99%
“…The volume administered was estimated considering the percentage of the spinal cord to be blocked, according to the mathematical model proposed by Otero et al 42 Reducing the systemic vascular resistance (SVR), the combination of epidural and general anaesthesia can decrease the need for vasodilatory drugs and has been associated with a lower risk of postoperative complications in human patients with PCC. 43,44 Epidural anaesthesia can also exacerbate intraoperative hypotension after tumour removal, 45 although this could be counteracted reducing the expired fraction of inhalant anaesthetic. 46,47 α 2 -adrenoceptor agonists (i.e., medetomidine or DEX) cause a dose-dependent increase of SVR and a decrease in CI.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the systemic vascular resistance (SVR), the combination of epidural and general anaesthesia can decrease the need for vasodilatory drugs and has been associated with a lower risk of postoperative complications in human patients with PCC 43,44 . Epidural anaesthesia can also exacerbate intraoperative hypotension after tumour removal, 45 although this could be counteracted reducing the expired fraction of inhalant anaesthetic 46,47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation